Working Through Memory and Forgetting in Victorian Literature - Douglas-Fairhurst, Robert (Australasian Journal of Victorian Studies, 2016)
Robert Douglas-Fairhurst's keynote address to the Australasian Victorian Studies Association's conference at The University of Auckland, New Zealand, 2015.